Allogeneic Mesenchymal Stem Cell Treatment Induces Specific Alloantibodies in Horses - Sean D. Owens; Amir Kol; Naomi J. Walker; Dori L. Borjesson (Stem Cells International)
Background. It is unknown whether horses that receive allogeneic mesenchymal stem cells (MSCs) injections develop specific humoral immune response. Our goal was to develop and validate a flow cytometric MSC crossmatch procedure and to determine if horses that received allogeneic MSCs in a clinical setting developed measurable antibodies following MSC administration. Methods. Serum was collected from a total of 19 horses enrolled in 3 different research projects. Horses in the 3 studies all received unmatched allogeneic MSCs. Bone marrow (BM) or adipose tissue derived MSCs (ad-MSCs) were administered via intravenous, intra-arterial, intratendon, or intraocular routes. Anti-MSCs and anti-bovine serum albumin antibodies were detected via flow cytometry and ELISA, respectively. Results. Overall, anti-MSC antibodies were detected in 37% of the horses. The majority of horses (89%) were positive for anti-bovine serum albumin (BSA) antibodies prior to and after MSC injection. Finally, there was no correlation between the amount of anti-BSA antibody and the development of anti-MSC antibodies. Conclusion. Anti allo-MSC antibody development was common; however, the significance of these antibodies is unknown. There was no correlation between either the presence or absence of antibodies and the percent antibody binding to MSCs and any adverse reaction to a MSC injection.